The Effect Of Impingement Hot Air On Temperature Distribution Of The Flat Plate - Kasim, Nor Asikin (Universiti Sains Malaysia, 2021)
Until recently, ice on an aircraft’s surface was seen as a severe aerodynamic and flight mechanical problem that may jeopardise aircraft flight safety. Hot air jet impingement is one method used to eliminate icing on critical aircraft surfaces such as the nacelle lip skin. However, due to the direct impact of the hot air jet on the nacelle lip skin, a hotspot was created. Thus, this project is concerned with a numerical study of the convective heat exchange between an impinging air jet at temperatures of 50° C, 55° C, and 60° C and a structured flat surface using the Fluent tool to reduce the hot spot on the surface. Standard k-ɛ model using the energy equation are carried out on a model jet in a three-dimensional domain with periodic boundary conditions. The range of jet Reynolds numbers utilised in the simulations is 2000–5000, while the jet-to-target distance remains constant at 37.05 mm using a circular 2.5 mm nozzle. The target plate is flat steel, copper, and aluminium plate with a 1 mm, 2 mm, and 3 mm thickness. The effect of Reynolds number impingement flow on temperature distributions on a flat plate can be seen that at 50°C for a 1 mm steel plate, the Reynolds number is raised to 4085.86, the